2021
DOI: 10.1093/jpepsy/jsab008
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Recruitment of Black Adolescents into Behavioral Research: A Multi-Center Study

Abstract: Objectives Adolescents of color are underrepresented in behavioral health research. Study aims were to quantify the amount and types of outreach effort needed to recruit young Black adolescents with type 1 diabetes and their primary caregiver into a clinical trial evaluating a parenting intervention and to determine if degree of recruitment difficulty was related to demographic, diabetes-related, or family characteristics. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…The aim is to reapproach families who may not have otherwise answered the phone or became unresponsive during remote recruitment. This hybrid model aligns with findings that persistent and varying methods of recruitment increase the participation of underrepresented racial and ethnic minorities in clinical research trials [9]. While the impact of COVID-19 on the future of clinical trials remains uncertain, we expect to see more clinical trials develop remote procedures to adjust to social distancing practices.…”
Section: Future Directionssupporting
confidence: 61%
“…The aim is to reapproach families who may not have otherwise answered the phone or became unresponsive during remote recruitment. This hybrid model aligns with findings that persistent and varying methods of recruitment increase the participation of underrepresented racial and ethnic minorities in clinical research trials [9]. While the impact of COVID-19 on the future of clinical trials remains uncertain, we expect to see more clinical trials develop remote procedures to adjust to social distancing practices.…”
Section: Future Directionssupporting
confidence: 61%
“…Bridging the gap between science and society allows for more representative, innovative and generalizable research, which may ultimately benefit healthcare practices, education and policy efforts (Ellis et al, 2021). Here, we provide some experience-and evidence-based recommendations to enhance diversity, equity, and inclusion in developmental human neuroscience through activities that are aimed at connecting science to society.…”
Section: Connecting Science To Societymentioning
confidence: 99%
“…Enrolling representative samples often requires different recruitment and retention approaches to engage particular populations. For example, Ellis et al ( 2021 ) reported the need for persistence in reaching out to some families of Black children with type 1 diabetes to make contact and recruit for clinical trials. Use of various contact approaches (e.g., mail, phone calls, texts, in-person) was critical in ensuring families were able to understand and participate in the research process; though in many cases, this persistence may not be common in the conduct of traditional research studies.…”
Section: Conducting Adherence Sciencementioning
confidence: 99%